The Effect of Substitution and Combinastion of Feed on The Growth And Survival Rate of Giant Gouramy Larvae (Osphronemus gouramy Lac.) - Syerfat Elvia Rahmi; Netti Aryani; Nuraini Nuraini (Jurnal Akuakultur SEBATIN, 2021)
This research was conducted on December 22 2019 – January 30 2020, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Universitas Riau. This study purposed to understand the effect of the best feed (Tubifex sp., water flees or synthetic feed ) to replace the first feed ( Artemia sp.) and the best feed combination to growth and survival rate of gouramy larvae. This study used Completely Randomized Design (CRD). Treatments used P1= Artemia sp. ( 11-20 days old ) + Water Fleas ( 21-30 days old ) + Tubifex sp. ( 31-40 days old ) + Artificial Feed ( 41-50 days old ), P2 = Artemia sp. ( 11-20 days old ) + Water Fleas ( 21-30 days old ) + Artificial Feed ( 31-40 days old ) + Tubifex sp. ( 41-50 days old ), P3 = Artemia sp. ( 11-20 days old ) + Tubifex sp. ( 21-30 days old ) + Water Fleas ( 31-40 days old ) + Artificial Feed ( 41-50 days old ), P4 = Artemia sp. ( 11-20 days old ) + Tubifex sp. ( 21-30 days old ) Artificial Feed ( 31-40 days old ) + Water Fleas ( 41-50 days old ), P5 = Artemia sp. ( 11-20 days old ) + Artificial Feed ( 21-30 days old ) + Water Fleas ( 31-40 days old ) + Tubifex sp. ( 41-50 days old ). P6 = Artemia sp. ( 11-20 days old ) + Artificial Feed ( 21-30 days old ) + Tubifex sp. ( 31-40 days old ). The research showed that the best feed to replace Artemia sp. is Tubifex sp. produced weight 0,57 g, length 2,53 cm, daily growth rate 9,54% days and survival rate 81,11%. Feed combination treatments affected on absolute weights, absolute length and daily growth rate but did not affect the survival rate of gouramy larvae. The water quality during the research temperatures 26,3-27,40 C, pH 6,5-7,3 and DO 4,3-6,0 ppm